EFFECTIVENESS OF ULTRASOUND (US), TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) AND STRETCHING IN PLANTAR FASCIITIS CASES: A CASE REPORT - Khotimah, Siti Nur; Pristianto, Arif; Rochmaningtyas, Putri (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Plantar Fasciitis (PF) is a standard heel and foot pain that affects the plantar fascia. The purpose of this study is to determine the effectiveness of ultrasound (US), Transcutaneous Electrical Nerve Stimulation (TENS), and stretching in treating Plantar Fasciitis cases. Case Presentation: The patient in this study was a 38-year-old man with complaints of medial heel press pain, wake-up pain in the morning and after activity. Management and Outcome: given therapy in ultrasound (US), Transcutaneous Electrical Nerve Stimulation (TENS), and stretching as many as four times. The pain was measured using a numeric rating scale (NRS) and the Foot and Ankle Outcome Score (FAOS). Discussion: After being given therapy, it obtained results in the form of pain reduction measured using the Numeric Rating Scale (NRS pain press T1: 5 to T4: 2, wake pain in the morning T1: 7 to T4: 3, pain after activity T1: 6 to T4: 3 and there was an increase in ability measured using FAOS (Foot and Ankle Outcome Score). Conclusion: The administration of ultrasound (US), Transcutaneous Electrical Nerve Stimulation (TENS), and stretching effective reduces pain and improves functional ability in patients with Plantar Fasciitis.